Pragmatic markers and events on social media in new habit era of COVID-19 outbreak - Fitriani, Rani Siti; Hidayati, R. Panca Pertiwi; Budiarti, Any (Linguistics and Culture Review, 2021)
The phenomenon of language use in social media is interesting and important because it can describe positive or negative language use. The purpose of the study was to analyze the pragmatic markers and forms of language use on social media in the era of new habits during the COVID 19 outbreak. The research method used a qualitative approach. The results of the study are: (1) religious markers, (2) pronoun markers, (3) interjection markers, and (4) appreciation markers. The form of pragmatics consists of, (1) the form of syntax, (2) the form of discourse, and (3) the form of strategy. Conclusion (1). Positive utterances from speakers are responded to by positive and negative utterances from speech partners, while (2). Negative speech from the speaker is responded to by negative speech from the speech partner. (3). The pragmatic markers and forms of speech by speakers are 50% positive and 50% negative, while the pragmatic markers and forms of speech partners are 30% positive and 70% negative. (4). Positive pragmatic markers and forms are important to be used by speakers and speech partners so that they will have an impact on positive and healthy social media.